Business Dynamics of Islamic Bank Mudharabah Contracts: An Islamic Economics Perspective - Putra, Hafiza; Syahrial, Murah (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This research examines how the concept of mudharabah in classical Islamic theory is implemented in Islamic monetary institutions, especially Islamic banking. Using literature research, this study shows that there are differences between the concept of mudharabah in classical fiqh books and its implementation in Islamic banking. implementation in Islamic banking. The difference indicates that the door to ijtihad ijtihad is still wide open in contemporary Islamic law. The principle of prudence requires Islamic banking to contextualise the classical concept of mudharabah in contemporary socio-cultural situations.